Levamisole-Induced immune phenomenon and its various clinical manifestations in children: Two case reports along with review of literature - Anu Punnen Kocheril; T Sathish Kumar; Dharshini Sathishkumar (Indian Journal of Rheumatology)
In literature, levamisole-induced immune manifestations were described mostly in association with its use in treatment of rheumatoid arthritis, malignancies, and recently, in relation to the use of illicit cocaine contaminated with levamisole among adults. Even though levamisole has been proven to be an inexpensive, safer, and effective drug with minimal side effects among children, it is not possible to undermine its potential side effects. The objective of this study was to describe levamisole-induced immune phenomenon and its manifestation in children. We describe two children with levamisole-induced immune phenomenon, leading to limb ischemia resulting in a gangrene and autoamputation of toes in the first child and an isolated microscopic hematuria in the second child along with a thorough review of available knowledge on this rare manifestation in children. Increased awareness of these rare but severe manifestations will remind clinicians to keep a high index of suspicion, its early recognizing, and withdrawal of offending drug before severe morbidity occurs in those children on levamisole.